Peningkatan Hasil Belajar Biologi Melalui Model Pembelajaran Rotating Trio Exchange (RTE) Pada Siswa Kelas XI SMA Negeri 23 Maluku Tengah: (Improving Biology Learning Outcomes Through the Rotating Trio Exchange Learning Model for Class XI Students of SMA Negeri 23 Maluku Tengah) - Wa Ode Sarwita; Kevin Tamaela; Pricilia Sopratu; Kalsum Selehulano (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
The purpose of this study was to improve the learning outcomes of biology through the rotating trio exchange learning model for class XI students of SMA Negeri 23 Maluku Tengah. This research was conducted in the 2020/2021 school year. This type of research is classroom action research. As a subject, students of class XI totaled 24 students. The research was carried out in 2 cycles and each cycle consisted of 4 stages, namely; planning, implementing, observing, and reflecting. The results obtained indicate that the application of the rotating trio exchange model carried out is evident from the completeness of the learning outcomes of the first cycle students by 25% and at the end of the second cycle has increased to 100%. The score of the observation of student learning activities in cycle I was 54.17%, and at the end of the second cycle it increased to 95.83%, which means that it was categorized as very good. Based on the research results obtained, it can be concluded that improving student learning outcomes can be improved by applying the rotating trio exchange model. Abstrak. Tujuan penelitian ini untuk meningkatkan hasil belajar biologi melalui model pembelajaran rotating trio exchange pada siswa kelas XI SMA Negeri 23 Maluku Tengah. Penelitian ini dilakukan tahun ajaran 2020/2021. Jenis penelitian yang digunakan adalah penelitian tindakan kelas. Sebagai subjek siswa kelas XI berjumlah 24 siswa. Penelitian telah dilaksanakan dalam 2 siklus dan masing-masing siklus terdiri dari 4 tahapan yaitu; perencanaan, pelaksanaan, observasi, dan refleksi. Hasil yang diperoleh menunjukkan bahwa penerapan model rotating trio exchange yang dilakukan terbukti dari ketuntasan hasil belajar siswa siklus I sebesar 25% dan pada akhir siklus ke-II mengalami peningkatan menjadi 100%. Adapun skor observasi aktivitas belajar siswa siklus I sebesar 54.17%, dan pada akhir siklus ke-II mengalami peningkatan menjadi 95.83%, yang artinya berkategori sangat baik. Berdasarkan hasil penelitian yang diperoleh maka dapat disimpulkan bahwa meningkatkan hasil belajar siswa dapat ditingkatkan dengan penerapan model rotating trio exchange.